1998
DOI: 10.1006/dbio.1998.9099
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Developmental Characterization of Cerebral Cortical Multipotent Progenitors

Abstract: Multipotent neural progenitor species present within developing and adult periventricular generative zones can give rise to all of the major cellular elements of the brain. Although lineage specification during development has been thought to be restricted to these generative zones, we have utilized quantitative immunoselection techniques to isolate an enriched population of multipotent neural progenitor cells that express polysialylated neural cell adhesion molecule (PSA-NCAM) from postnatal day 2 cerebral co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 46 publications
4
74
0
Order By: Relevance
“…Indeed, we also found that cells isolated from all the regions of the cortical parenchyma at early postnatal (P8) stages generate primary neurospheres, in accordance with our BrdU labeling at this stage (supplemental Fig. 3, available at www.jneurosci.org as supplemental material) and previous data in the literature (Marmur et al, 1998;Belachew et al, 2003). However, although we detect slowly dividing cells in the adult cortex, no neurospheres can be derived any longer from the cortical parenchyma, including the layer 1 (data not shown).…”
Section: Clonal Analysis Of the Progeny Derived From Cells Proliferatsupporting
confidence: 90%
“…Indeed, we also found that cells isolated from all the regions of the cortical parenchyma at early postnatal (P8) stages generate primary neurospheres, in accordance with our BrdU labeling at this stage (supplemental Fig. 3, available at www.jneurosci.org as supplemental material) and previous data in the literature (Marmur et al, 1998;Belachew et al, 2003). However, although we detect slowly dividing cells in the adult cortex, no neurospheres can be derived any longer from the cortical parenchyma, including the layer 1 (data not shown).…”
Section: Clonal Analysis Of the Progeny Derived From Cells Proliferatsupporting
confidence: 90%
“…Despite being downregulated after birth, PSANCAM remains elevated in neurogenic areas [34] and has been used to isolate from various brain regions highly proliferative precursors displaying multipotency in vitro [36,37] and in vivo [38]. In particular, Marmur et al found that in the postnatal cortex all multipotent precursors are PSANCAM þ , whereas in the SVZ the multipotent cells equally consist of PSANCAM À and PSANCAM þ precursors.…”
Section: Both Stem Cells and Neuroblasts Express Psancammentioning
confidence: 99%
“…Although they are already restricted to either a glial (Trotter et al, 1989;Grinspan and Franceschini, 1995;Ben Hur et al, 1998;Vitry et al, 1999) or a neuronal (Mayer-Proschel et al, 1997) preferential fate, cultured PSA-NCAM ϩ progenitors preserve a relative degree of pluripotentiality (Marmur et al, 1998;Vitry et al, 2001). Considering that PSA-NCAM ϩ cells can be neatly used for brain repair purposes (Keirstead et al, 1999;Vitry et al, 2001), there is much interest in studying signaling factors that regulate their development.…”
Section: Introductionmentioning
confidence: 99%